IMPROVING STUDENTS’ WRITING ABILITY THROUGH COOPERATIVE LEARNING TYPE JIGSAW - Purna Wiratno (JETA (Journal of English Teaching and Applied Linguistic), 2020)
The object of this research is to find the improving students writing ability through cooperative learning type jigsaw at SMP level. The research was conducted in SMP N 3 Katibung, Lampung selatan in 2018/2019. The research was conducted at the second semester in the academic year of 2018-2019. The subject of research was students at the second semester of the eight B class of SMP N 3 Katibung, Lampung Selatan in the academic year of 2018/2019. It consists 25 students. In conducting this research, the writer used classroom action research method. This method used to improve student writing ability through cooperative learning type jigsaw. The writer used one class in this research. The data analysis research finding, the writer concludes that students’ writing ability of the eighth class of SMP N 03 Katibung Lampung Selatan increased. It can be seen from the result of the second cycle which has mean score 74.8, it was better than in cycle I which has mean score 68.64.Teaching learning process using cooperative learning type jigsaw became active and Cooperative learning type jigsaw is one of the suitable techniques in teaching writing. By applying this technique, the students can improve their writing skill. This technique helps the students in making composition about narrative text with good structural.